Rally pace and match characteristics of male and female tennis matches at the Australian Open 2017 - Carboch, J.; Placha, K.; Sklenarik, M. (Journal of Human Sport & Exercise, 2018)
Tennis players hit very fast shots during matches and the opponent needs to hit the ball back within a limited time. The aim of this paper is to analyse the rally pace characteristics and the frequency of rally shots in the men`s and women`s matches at the Australian Open 2017. We analysed male (n=7) and female (n=23) matches at Australian Open 2017. We compared the (1) point duration; (2) number of rally shots; (3) time between the points; (4) rally pace; and (5) work to rest ratio. In spite of some small differences between the men`s and women`s matches, such as work to rest ratio (men 1:3,63±0,38; women 1:4,05±0,73), point duration (men 5,93±0,67 s; women 5,44±1,11 s) and rally shots number (men 4,85±0,48; women 4,47±0,72), none of these differences were significant. Both genders played at the same rally pace (while the ball is in the play), which was 1.2 s (mean ball flight time between the opponents). About 60 % of rallies were finished within the first four shots of the rally. Our findings could help coaches to utilize the practice sessions prior to the Australian Open tournament.